PENGARUH SUBTITUSI SLAG NIKEL DAN FLY ASH TERHADAP KUAT TEKAN BETON SEBAGAI PEMECAH GELOMBANG - Sukarman; Erlina Yanuarini; Lilis Tiyani; Shofie Rania Salsabila; Viona Seren (Universitas Widyatama, 2022)
Abstract Nickel slag is effluent from the nickel ore waste management process which has no economic value. Based on the visual aspect, nickel slag has a physical form that resembles coarse or fine aggregate. The chemical composition of the most nickel slag is silica with a percentage of 41.47% which is expected to strengthen the hydration process and increase the compressive strength of concrete. Concrete treatment is one of the things that can affect the strength of concrete. Concrete treatment generally uses water that is free from chemical and other substances that can affect the quality of concrete. Concrete in buildings located around the sea will experience direct contact with sea water, while sea water contains elements of salt and high chemical content which can cause a decrease in the quality of concrete. This decrease in the quality of concrete will affect the mechanical properties of the concrete, especially the compressive strength of the concrete itself. Therefore, this study aims to identify the effect of using nickel slag as a substitute for coarse aggregate with seawater immersion on the compressive strength of concrete. The method in this study is using the experimental method by making 48 concrete specimens with 4 variations, namely B.BP, L.BP, B.SN, and L.SN with testing the compressive strength of concrete at the age of 7, 14, 21, and 28 days. The results of the compressive strength test at the age of 7.14, and 21 days, the highest percentage of the compressive strength of concrete was 58.25%; 50.06%; 35.93%; on the variation of B.SN to the variation of B.BP, while at the age of 28 days the variation of L.SN experienced an increase in the compressive strength of concrete by 18.54% against the variation of B.BP. Keywords: Compressive strength; nickel slag; sea water; soaking; subtitution